Clinical efficacy of antiviral agents against coronavirus disease 2019: A systematic review of randomized controlled trials - Lai, Chih-Cheng (J Microbiol Immunol Infect, 2021)
Despite aggressive efforts on containment measures for the coronavirus disease 2019 (COVID-19) pandemic around the world, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is continuously spreading. Therefore, there is an urgent need for an effective antiviral agent. To date, considerable research has been conducted to develop different approaches to COVID-19 therapy. In addition to early observational studies, which could be limited by study design, small sample size, non-randomized design, or different timings of treatment, an increasing number of randomized controlled trials (RCTs) investigating the clinical efficacy and safety of antiviral agents are being carried out. This study reviews the updated findings of RCTs regarding the clinical efficacy of eight antiviral agents against COVID-19, including remdesivir, lopinavir/ritonavir, favipiravir, sofosbuvir/daclatasvir, sofosbuvir/ledipasvir, baloxavir, umifenovir, darunavir/cobicistat, and their combinations. Treatment with remdesivir could accelerate clinical improvement; however, it lacked additional survival benefits. Moreover, 5-day regimen of remdesivir might show adequate effectiveness in patients with mild to moderate COVID-19. Favipiravir was only marginally effective regarding clinical improvement and virological assessment based on the results of small RCTs. The present evidence suggests that sofosbuvir/daclatasvir may improve survival and clinical outcomes in patients with COVID-19. However, the sample sizes for analysis were relatively small, and all studies were exclusively conducted in Iran. Further larger RCTs in other countries are warranted to support these findings. In contrast, the present findings of limited RCTs did not indicate the use of lopinavir/ritonavir, sofosbuvir/ledipasvir, baloxavir, umifenovir, and darunavir/cobicistat in the treatment of patients hospitalized for COVID-19.